The Impact of Artificial Intelligence on Human Resource Management in the Era of Digitalization - PhD. Mugur TOLICI1; PhD. Daniela NICULESCU (Revista de Management Comparat International)
Artificial Intelligence (AI) is transforming Human Resource Management (HRM) by enhancing efficiency, decision-making, and employee engagement. This study examines AI-driven HR functions, including recruitment, performance evaluation, and learning and development, while addressing ethical and operational challenges such as bias, data privacy, and job displacement. Using a qualitative methodology, including a narrative literature review and case study analysis, the research explores AI’s integration within HRM through theoretical frameworks such as the Technology Acceptance Model (TAM), Resource-Based View (RBV), and Socio-Technical Systems Theory. The study presents a Conceptual Model for AI Integration in HRM, emphasizing alignment with organizational culture, ethical governance, and regulatory compliance. Findings suggest that while AI optimizes HR processes, responsible implementation is essential to ensure fairness and workforce well-being. Future research should focus on ethical AI governance and industry-specific adoption strategies to maintain a balance between automation and human-centric HR practices.